Improved performance of lithium–sulfur batteries by employing a sulfonated carbon nanoparticle-modified glass fiber separator. Issue 15 (30th June 2021) - Ponnada, Srikanth; Kiai, Maryam Sadat; Gorle, Demudu Babu; Nowduri, Annapurna
Abstract : Lithium–sulfur batteries with novel sulfonated coating glass fiber separator with high energy density and theoretical capacity. Abstract : Some of the most promising alternatives in the energy storage sector are lithium–sulfur batteries, which have a high energy density and theoretical capacity. However, the low electrical conductivity of sulfur and the shuttle effect of polysulfides remain important technical obstacles in the practical use of lithium–sulfur batteries (LSBs). This work employed a glass fiber separator with sulfonated carbon nanoparticles (SCNPs) to reduce the shuttle effect. The negatively charged sulfonic groups in SCNPs might prevent polysulfide migration and anchor lithium polysulfides. By using carbon-based interlayers, this method improves ion conductivity. Furthermore, the equally scattered sulfonic groups serve as active sites, causing sulfur to be distributed consistently and limiting sulfur growth while enhancing active sulfur utilization. After 200 cycles at 1C, the SCNP separator-containing cell showed a specific capacity of 1080 mA h g −1 . After 200 cycles, the cell with a CNP separator only showed a specific capacity of 854 mA h g −1, demonstrating that CNPs' polysulfide diffusion suppression was ineffective. The cell with the SCNP separator still showed a high capacity of 901 mA h g −1 after 500 cycles, with an average coulombic efficiency of almost 98%.